Hydromorphological river assessment of degraded land in the region of open cast mines = Ocena stanu hydromorfologicznego rzek terenów zdegradowanych w rejonie kopalń odkrywkowych - Adynkiewicz-Piragas, Mariusz; Lejcuś, Iwona (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
River and floodplains form one of the most valuable elements of the surrounding landscape. Over the centuries, anthropogenic impacts have led to numerous transformations of river ecosystem. Following this study, river beds noted the need for corrective action and renaturalisation. Therefore, there was a need to assess the current state of watercourses.
Keywords: ocena stanu rzek; obszary zalewowe; tereny zdegradowane; river; hydromorphology; river bed